Can Low- and Middle-Income Countries Increase Domestic Fiscal Space for Health: A Mixed-Methods Approach to Assess Possible Sources of Expansion - Helene Barroy; Susan Sparkes; Elina Dale; Jacky Mathonnat (Taylor & Francis Group, 2018)
Abstract-There has not been a systematic effort to synthesize findings of domestic fiscal space for health (DFSH) assessments, despite the existence of a commonly applied conceptual framework. To fill this gap and provide support to policy makers designing health financing policies toward universal health coverage (UHC), this study uses both qualitative and quantitative methods to assess the scope of possible sources of DFSH in low- and middle-income countries (LMICs). First, the findings of 28 studies assessing DFSH in LMICs were reviewed. A quantitative assessment was then conducted to assess potential expansion from increased tax revenues, a greater prioritization of health in the overall budget, and improved technical efficiency of health spending in a sample of 64 LMICs. The analysis found that macroeconomic conditions and budget prioritization are the key sources of DFSH expansion in 90% of the reviewed studies. Improved efficiency was referenced as having high potential for DFSH expansion in 60% of the studies. The quantitative analysis converged with these findings and further confirmed that an increase in tax revenues is, on average, the largest source of potential DFSH expansion (95% confidence interval [CI], 60%, 96%) in the studied countries. However, even without injecting new revenues, reprioritization of budget and technical efficiency improvements could significantly expand DFSH (95% CI, 77%, 102%). While highlighting the critical role played by fiscal conditions and tax policies, the study provides strong rationale for explicitly incorporating efficiency as a core source of DFSH in a more systematic manner in future assessments.